Evaluation of some edible leaves as potential feed ingredients in aquatic animal nutrition and health - Olusola, Sunday Emmanuel; Olaifa, Flora Eyibio (Journal of Fisheries, 2018)
In this study, the potential benefits of ten edible leaves (Manihot esculents, cassava leaf; Colocasia esculenta, cocoyam leaf; Talinum triagulare, water leaf; Telfairia occidentalis, fluted pumpkin leaf; Carica papaya, pawpaw leaf; Amaranthus chlorostachys, green leaf; Moringa oleifare, drumstick leaf; Vernonia amygdalina, bitter leaf; Ipomoea batatas, sweet potato leaf and Basella alba, Malabar spinach ‘Amunututu’ to aquatic animal nutrition and health were studied along with proximate, mineral and phytochemical compositions. Results show that theses edible leaves were a good source of protein and the highest crude protein was obtained in C. papaya (32.6%) while the lowest in C. esculenta (14.7%). The highest and lowest total ash was found in T. triagulare (34.6%) and C. papaya (11%) respectively. The result showed that the edible leaves are rich in wide variety of secondary metabolites of phytochemical constituents such as tannins, alkaloids, flavonoids, saponins, glycosides oxalates and phytate which can act against different diseases. Results suggest that inclusion of edible leaves may be nutritionally beneficial and this could promote growth, immune system and enhance disease resistance properties and subsequently very potential to reduce the cost of highly priced supplementary feeds.